2018
DOI: 10.18203/2349-3933.ijam20181661
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profiles among Plasmodium falciparum infected, non malarial febrile patients and volunteers

Abstract: Background: Acute falciparum Malaria infected patients show wide ranges of metabolic derangement including changes in serum lipid profiles. The exact mechanisms of this derangement in serum lipid profiles are still poorly understood. Objective was to study the lipid profiles among acute plasmodium falciparum infected patients.Methods: It was a Prospective observational comparative study. A total of 100 patients were consecutively taken in the study. Fifty Non- malaria febrile cases and 50 healthy volunteers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…Except for HDL, these study results are in line with a study reported from Nigeria where TG(0.170), TC (0.18), HDL (2.36), and LDL (-2.7) mg/dl were reported; in Gabon where TC(-12.98), HDL-C (-9.55); LDL(-9.96),and TG levels (0.9) were reported (22,41) in mg/dl of mean difference of pre-and post-treatment, respectively. The mean difference in our findings is inconsistent with the mean difference of other study reports from Nigeria where HDL(1.28), LDL (5.51),TG(4.41),and TC(-6.49) (42), and in India where TC(-12.34),HDL(-1.44), LDL (-3.19) and TG (11.42), respectively (43).The possible explanation for this variation might be due to the physiological, environmental, host immunity, and nutritional status differences.…”
Section: Serum Liver Enzymes and Lipid Profiles In Different Level Of Parasitaemia Among Malaria-infected Patients Before Anti-malaria Trcontrasting
confidence: 99%
“…Except for HDL, these study results are in line with a study reported from Nigeria where TG(0.170), TC (0.18), HDL (2.36), and LDL (-2.7) mg/dl were reported; in Gabon where TC(-12.98), HDL-C (-9.55); LDL(-9.96),and TG levels (0.9) were reported (22,41) in mg/dl of mean difference of pre-and post-treatment, respectively. The mean difference in our findings is inconsistent with the mean difference of other study reports from Nigeria where HDL(1.28), LDL (5.51),TG(4.41),and TC(-6.49) (42), and in India where TC(-12.34),HDL(-1.44), LDL (-3.19) and TG (11.42), respectively (43).The possible explanation for this variation might be due to the physiological, environmental, host immunity, and nutritional status differences.…”
Section: Serum Liver Enzymes and Lipid Profiles In Different Level Of Parasitaemia Among Malaria-infected Patients Before Anti-malaria Trcontrasting
confidence: 99%
“…26,46 The mean difference in our findings is inconsistent with the mean difference of other study reports from Nigeria where HDL (1.28), LDL (5.51), TG (4.41), and TC (−6.49), 47 and from India where TC (−12.34), HDL (−1.44), LDL (−3.19) and TG (11.42), is reported respectively. 48 The possible explanation for this variation might be due to the physiological, environmental, host immunity, and nutritional status differences.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, P. vivax -infected patients were observed to have lower TC, LDL, and HDL levels while having higher TAG levels when compared to normal/apparently healthy individuals ( Mesquita et al, 2016 ). Falciparum malaria has also been associated with decreased levels of HDL, LDL, and total cholesterol as well as increased or unaltered levels of TAGs and very low-density lipoproteins (VLDL) ( Kullu et al, 2018 ). Of note, following antimalarial medication therapy, these changes in lipid levels normalized along with a significant decrease in parasitemia and the eradication of clinical symptoms of malaria.…”
Section: Resultsmentioning
confidence: 99%